Removal of synthetic dye from water by chlorella vulgaris microalgae - Chin, Jian Yean (2019)
Textile dyeing is in the ranking number 2 of the polluter of fresh water. To prevent the coloured waste water to be discharged which polluted the environment, the coloured waste water commonly will be treated to the acceptance level which was comply with the environmental protection laws before discharged to the environment. Microalgae is one of the potential method that can remove the textile dyes from the wastewater. It is a promising alternative solution to remove the textile dyes because it is clean, environmental friendly and reduce the greenhouse gases. Moreover, the biomass of microalgae can be produce as biofuels and contain many nutrients that benefits to human. However, the properties of synthetic dyes will affect the potential of bioadsorption, biodegradation or bioconversion of dye by microalgae. Therefore, the study onto different synthetic dye with different property is important to investigate the dye removal mechanism used by microalgae. In this study, Chlorella vulgaris microalgae is used to remove two synthetic dyes with different surface charge that are methylene blue which is positive surface charge and acid orange 7 which is negative surface charge. Results show that the microalgae able to remove the methylene blue by electrostatic interaction through adsorption while the acid orange 7 dye is not able to be removed. The highest removal efficiency of methylene blue was at initial concentration of 100mg/L which was 83.04 ± 2.94% at day 3. The removal mechanism used by the microalgae was more favour towards Langmuir isotherm with 128.21mg/g maximum adsorption capacity (qmax), 0.0096L/mg adsorption equilibrium constant (KL) and 0.8216 R2 value. The incubation period was prolonged to 4 weeks for initial concentration of 50mg/L and 100mg/L methylene blue was done and found out that dye removal efficiency had reached to stationary state after incubated for 1 week. The cell density in this both concentration were found decrease during the incubation period. Biochemical composition of the microalgae were studies after the treatment of the synthetic dye. Result showed that the total protein, total carbohydrates and total chlorophyll were the highest at week 1 which were 46.65 ± 2.6 mg/L, 73.33 ± 40.55 mg/L and 247.31 ± 17.88 mg/L at 100mg/L initial concentration of methylene blue.